Patterns of tobacco smoking among illicit drug users in Australia 2001–2010. (29th July 2014) - Fraser, Doug; Gartner, Coral; Hall, Wayne
Abstract Introduction and Aims This study aimed to investigate whether there were changes from 2001 to 2010 in the characteristics of young adults who used party drugs or other illicit drugs and to determine if the prevalence of tobacco smoking differed depending on the type of drugs used. Design and Methods We analysed confidentialised data from the 2001 and 2010 National Drug Strategy Household Surveys. We compared young adults (aged 18–29) who used party drugs to other drug users and non‐users on demographic variables. We assessed relationships between (i) illicit drug use and smoking; (ii) illicit drug use and smoking while controlling for social and demographic differences; and (iii) illicit drug use and smoking after controlling for social and demographic variables along with cannabis and alcohol use. Results There was little difference between 2001 and 2010 in drug user characteristics and smoking. Party drug users were more educated and of higher socioeconomic status than illicit drug users and non‐users. Party drug users and users of other illicit drugs were far more likely to smoke tobacco; however, a large part of this relationship was explained by the higher rate of cannabis and alcohol use in these groups. Discussion and Conclusions Over the last decade, party drug users have been a relatively socially advantaged sub‐population, yet smoking prevalence among these and other drug users has remained higher than among non‐users. This might be explained by the common sequence of drug involvement in which people initiate smoking, then cannabis use and followed by other drugs. [Fraser D, Gartner C, Hall W. Patterns of tobacco smoking among illicit drug users in Australia 2001–2010. Drug Alcohol Rev 2014;33:534–9]